Surgical Outcome Following Meningioma Operation: Our Experience from a Tertiary Care Hospital - Khalil, Md Ibrahim; Farazi, Md Mohsin Ali; Haque, Md Fazlul; Salam, Abdus; Sheikh, Md Sayedur Rahman (Bangladesh Journal of Neurosurgery, 2020)
Background: Meningiomas are the commonest predominantly non malignant brain tumour in adult. Various epidemiological and risk factors are associated with and influencing surgical outcome in the treatment of meningiomas. Objective: The aim of the study is assess surgical oucome by using Glasgow Outcome Scale (GOS) for the cranial meningiomas. Materials and Methods: This prospective study conducted in Neurosurgery Department of Shaheed Shiek Abu Naser Specialized Hospital and others private Medical Colleges in Khulna from Jan 2018 –July2019. Total 21 patients with meningioma underwent surgery are included in the study .The parameters analyzed included age, gender, location of tumor on imaging, histopathological type, and grade of tumor according to the 2007 WHO classification. The surgical outcome was assessed by the Glasgow Outcome Scale (GOS) at the end of the 1st week of convalescence and after 6 weeks following surgery. Favorable and unfavorable outcomes were defined as GOS 4- 5 and GOS 1–3, respectively. Results: Meningiomas are more common in the age group of 40-49 with a female preponderance(61.90%).Headache was the most common symptom and convexity meningiomas were the most common accounting for about 42.85%. Simpson grade I aceieved 10 (47.61%). Simpson II 5(23.80%), Simpson III 2(9.52%), Simpson IV 3(14.28%) and Simpson V 1(0.5%) respectively. Regarding Histopathologcal examination most of the tumours were WHO grade 1(85.71%). Surgical outcome assess by Glasgow Outcome Scale and majority of patients of this study GOS were between 4-5 which was good( 90.47%). Conclusion: The outcome for patients with meningioma is good and is improving. However there remains a significant mortality related to disease process. Bang. J Neurosurgery 2020; 10(1): 57-61